2019
DOI: 10.1038/s41467-019-09343-2
|View full text |Cite
|
Sign up to set email alerts
|

The neural computation of inconsistent choice behavior

Abstract: Humans are often inconsistent (irrational) when choosing among simple bundles of goods, even without any particular changes to framing or context. However, the neural computations that give rise to such inconsistencies are still unknown. Similar to sensory perception and motor output, we propose that a substantial component of inconsistent behavior is due to variability in the neural computation of value. Here, we develop a novel index that measures the severity of inconsistency of each choice, enabling us to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
79
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(92 citation statements)
references
References 69 publications
(114 reference statements)
10
79
1
Order By: Relevance
“…Our results thus differ from a previously reported vmPFC baseline-shift additive effect in pleasantness ratings (Abitbol et al, 2015;Lopez-Persem et al, 2020). Altogether, our results indicate that part of the unspecified 'neural noise' driving fluctuations in choice consistency (Padoa-Schioppa, 2013;Kurtz-David et al, 2019;Webb et al, 2019) comes from the interaction between interoceptive self-related processes, indexed by neural monitoring of cardiac signals, and the neural encoding of subjective value. A more detailed mechanistic account of how responses to heartbeat during task preparation influence the subjective valuation process taking place about 1.5 second later remains to be established.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results thus differ from a previously reported vmPFC baseline-shift additive effect in pleasantness ratings (Abitbol et al, 2015;Lopez-Persem et al, 2020). Altogether, our results indicate that part of the unspecified 'neural noise' driving fluctuations in choice consistency (Padoa-Schioppa, 2013;Kurtz-David et al, 2019;Webb et al, 2019) comes from the interaction between interoceptive self-related processes, indexed by neural monitoring of cardiac signals, and the neural encoding of subjective value. A more detailed mechanistic account of how responses to heartbeat during task preparation influence the subjective valuation process taking place about 1.5 second later remains to be established.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the importance of value-related regions for choice consistency finds additional support in the function brain imaging study of Kurtz-David et al (2019). Kurtz-David et al (2019) used the experimental task of Choi et al (2014) for a total of 108 trials. The study found that trialspecific choice inconsistency is correlated to functional activity in the ventro-medial prefrontal cortex, the anterior and the posterior cingulate cortex.…”
Section: Incomementioning
confidence: 99%
“…Few studies have tackled the question of how certain factors might influence choice consistency, which is especially relevant from a cognitive psychologist and neuroscientific point of view. A positive mention deserve the few studies investigating the neural underpinnings of choice inconsistency (Camille et al, 2011;Chung et al, 2017;Kalenscher et al, 2010;Kurtz-David et al, 2019), which suggest that value-encoding regions play a key role. Future studies should use a more theory-driven approach to identify moderators of choice consistency.…”
Section: Process Modelsmentioning
confidence: 99%
“…Severity in these symptom domains and difficulty forming biases consistent with past experience have been associated with altered prefrontal and striatal activity and connectivity (Gold et al, 2008;Simon et al, 2010;Arrondo et al, 2015). Recent work by Kurtz-David et al (2019) showed that in healthy adults, severity of trial-bytrial inconsistency between expectations and responses was associated with greater activity in the ventromedial prefrontal and anterior cingulate cortex, but not the ventral striatum. These early findings suggest that noise in select prefrontal regions might represent trait-level risk for pathological behavior.…”
Section: Review Ofmentioning
confidence: 99%